KEANEKARAGAMAN JAMUR MAKROSKOPIK DI KAWASAN TAMAN WISATA ALAM PERMISAN, KABUPATEN BANGKA SELATAN - Rahmad Lingga; Firsty Vanezza Gabriela; Mutiara Darlingga (Department of Biology, Faculty of Agriculture, Fisheries and Biology, University of Bangka Belitung, 2019)
Fungus is one of the main biotics component in ecosystem, included forest. The played a significant role in organic material decomposition. The present study aimed to obtained the presence of macroscopic fungus in TWA Permisan. We explored the presence of macroscopic fungus using exploration method. We found 23 species of macroscopic fungus divided into two Phylla i.e. Basidiomycota and Ascomycota. There were 13 species of macroscopic fungi which were live in dead wood and 10 species live on the ground and litter. Data on fungus biodiversity is very usefull for management and conservation effort of forest resources.